1998
DOI: 10.1074/jbc.273.51.34391
|View full text |Cite
|
Sign up to set email alerts
|

A Mycoplasma fermentans-derived Synthetic Lipopeptide Induces AP-1 and NF-κB Activity and Cytokine Secretion in Macrophages via the Activation of Mitogen-activated Protein Kinase Pathways

Abstract: Mycoplasma lipoproteins have been demonstrated to stimulate monocytic cells and induce proinflammatory cytokine secretion. In this paper, we show that a synthetic analog of the Mycoplasma fermentans membraneassociated lipopeptide macrophage-activating lipopeptide-2 (MALP-2) induces mRNA synthesis and protein secretion of interleukin-1␤ and tumor necrosis factor-␣ in human monocytes/macrophages and the murine macrophage cell line RAW 264.7, whereas the nonlipidated counterpart lacks this effect, underscoring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 41 publications
4
85
0
3
Order By: Relevance
“…The mechanisms involved in NO and TNF induction by mycoplasmas are poorly understood. Recently, it was shown that mycoplasma activates the transcription factor NF-B in DMBM-3 macrophage cell line [15] and induces transactivation of NF-B and AP-1 in the Raw 264.7 macrophage cell line [14]. It was also reported that Mycoplasma fermentans induces protein tyrosine phosphorylation [31] and activation of the three subgroups of mitogenactivated protein kinases (MAPKs), ERK 1/2, JNKs, and MAPK p38, and that induction of TNF production by mycoplasma involves the ERK 1/2 and p38 kinases [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms involved in NO and TNF induction by mycoplasmas are poorly understood. Recently, it was shown that mycoplasma activates the transcription factor NF-B in DMBM-3 macrophage cell line [15] and induces transactivation of NF-B and AP-1 in the Raw 264.7 macrophage cell line [14]. It was also reported that Mycoplasma fermentans induces protein tyrosine phosphorylation [31] and activation of the three subgroups of mitogenactivated protein kinases (MAPKs), ERK 1/2, JNKs, and MAPK p38, and that induction of TNF production by mycoplasma involves the ERK 1/2 and p38 kinases [13].…”
Section: Discussionmentioning
confidence: 99%
“…Its structure was elucidated and it constitutes one of the most potent macrophage stimulators [11] together with a lipopeptide recently isolated from M. hyorhinis membranes [12]. The characterization of mycoplasma-derived lipopeptides brought new insights into the mechanisms of NO and TNF induction in macrophages stimulated with mycoplasmas [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic lipopeptide corresponding to the N termini of the Treponema pallidum 47-kDa lipoprotein (designated 47-L) was a gift from J. Radolf (University of Connecticut, Farmington, CT). Synthetic lipopeptide based on the full-length MALP-2 membrane lipopeptide from Mycoplasma fermentans (sMALP-2) was a gift from G. Rawadi (Institut Pasteur, Paris, France) (27,42). Soluble peptidoglycan (designated sPG) was a gift from R. Dziarski (Indiana University School of Medicine, Gary, IN).…”
Section: Reagentsmentioning
confidence: 99%
“…Little is known about the signal pathways or the cell-surface receptors for MALP-2, except that MALP-2 activates the nuclear transcription factor NF-B (11,12). A new class of receptors of the innate immune system, the so-called Toll-like receptors (TLRs), was recently discovered (13)(14)(15), which recognize various bacterial cell-wall components such as LPS, peptidoglycan (PGN), LTA, and lipoproteins/lipopeptides (16 -22).…”
mentioning
confidence: 99%